Young adults with cerebral palsy as research partners - a qualitative evaluation of a mentoring program. - Cotton, Alexandra; Koder, Jordan; Harris, Sera; Wallen, Margaret (Developmental Neurorehabilitation)
Background and Objective: Research which will have a meaningful impact for young people with CP needs to be informed by individuals with lived experience so that issues and outcomes that are important for people with CP are prioritized. These consumer research partners (CRP) may experience barriers and facilitators which influence the productivity and authenticity of their involvement. A mentor program was implemented to support young adults with cerebral palsy (CP) in their roles as CRP. This study aimed to explore the mentor program from the perspectives of the CRP and mentors regarding aspects they found beneficial, unhelpful, or that needed improvement. Methods: Qualitative description guided the study. Participants were CRP and mentors contributing to a CP-specific research group, CP-Achieve, who participated in semi-structured interviews. Results: Six CRP (four females, two males) aged between 21 and 30 years of age (median = 23), and eight mentors/potential mentors (five females, two males, one preferred not to specify) aged between 28 and 39 years (median = 32.5) participated in the study. CRP identified that mentoring helped develop confidence in, and benefits beyond, their role. Mentors recognized the need to establish effective partnerships and skills which assisted in their role, and identified benefits and challenges. Themes common to both groups were a desire to improve and develop the mentor program, strategic use of technology and that one's own characteristics contributed to a successful mentoring relationship. Discussion: The findings of this evaluation contribute to research about the implementation and experience of mentor programs from the perspective of young adults living with CP and their mentors. The mentor program appeared to be of benefit to both mentors and mentees. The study has provided recommendations to inform revision and development of the mentor program to optimize the experience for participants, and the impact of CRP, including enhancing matching and orientation to roles, clarity of expectations, ongoing monitoring and support for mentors and mentees, and orchestrating formal closure of mentor relationships. The sample represented fewer than half of potential participants and did not include perspectives of young adult CRP who had chosen not to work with a mentor.